Performance of Barbari goats under different systems - PATEL, M S; SINGH, N P; GEHLAUT, B S; SINGH, H S (The Indian Journal of Animal Sciences, 2014)
The physiological responses of goats were measured weekly in the morning and evening during summer and winter. Significantly (P< 0.01) higher rectal temperature was observed in the morning in summer as compared to that in the winter in both grazing and stall-feeding groups. The evening rectal temperature was, on the other hand, significantly (P <0.01) higher in both the seasons and under both management conditions. Similar results were obtained for respiration rates. However, for pulse rate, the results were not so conspicuous as for the other physiological parameters; Significant differences were recorded for glucose values only during summer between the 2 management systems and only under stallÂ feeding between 2 seasons. Total protein, albumin and globulin concentrations were significantly higher (P < 0.01) in summer, but there was no significant difference in these values under the 2 management practices of feeding.